A Model for Handling Bullying in Schools by Involving Parents to Recognize and Address It - Nunung Suryana Jamin; Yelly Andriani Barlian; Naila Fikrina Afrih Lia (Universitas Pendidikan Ganesha, 2026)
Children’s behavior is fundamentally influenced by the family environment. However, family conflict, such as arguments between parents or between parents and children, can shape aggressive behavior patterns that carry over into the school environment. This study aims to analyze the relationship between family conflict and bullying behavior among secondary school students. The study employed a quantitative approach with a correlational design involving 370 students as the sample. Data were collected through a closed-ended questionnaire developed based on indicators of family conflict and bullying behavior variables. Data analysis was conducted using descriptive statistics to describe the level of each variable and the Pearson Product Moment correlation test to examine the relationship between variables. The results showed that both family conflict and bullying behavior were in the moderate category. The correlation test revealed a strong and significant positive relationship between family conflict and bullying behavior. The findings also indicate that the higher the level of family conflict, the greater the tendency for students to engage in bullying, particularly in non-physical forms such as intimidation and social exclusion. This study concludes that the family environment plays a crucial role in shaping students’ social behavior, with implications for the need for collaboration between schools and parents to foster harmonious communication and develop strategies to prevent aggressive behavior.